Bewertung der Verlässlichkeit: Neue Schweizer Ergebnisse. - König, Arnd; Axhausen, Kay (Deutscher Verkehrs-Verlag, 2005)
Unser heutiges Geschäftsleben und Gesellschaftssystem sind von zeitlichen Abhängigkeiten geprägt. Die Zeit ist als hochwertiges Gut etabliert. In der planerischen Praxis wird die mittlere Veränderung der Reisezeiten schon lange monetarisiert und bewertet. Es geht den Reisenden aber nicht nur um die Mittelwerte, sondern auch um deren Verlässlichkeiten. Der Beitrag zeigt auf, wie auch diese systematisch bewertet und monetarisiert werden können. difu

Current transport models focus mainly on the variables travel time and travel costs to explain choices made by travellers. In contrast to this, research results substantiate the influence of a wide range of additional explanatory variables. The reliability of the transportation system is one important example. The inclusion of those variables into the forecasting of travellers choice requires more knowledge about their valuations. This article gives an overview of a study performed at the Swiss Federal Institute of Technology (ETH), Zurich, where reliability was considered explicitly in the utility functions of the discrete choice models estimated. The willingness to pay for the reduction of delays and their probability was also estimated. difu
Keywords: Verkehr; Verkehrsplanung; Verkehrsmodell; Bewertungsmodell; Verkehrstheorie; Datenerhebung; Methode; Reisezeit; Verkehrsmittelwahl; Messinstrument; Verkehrsanalyse; Verkehrsteilnehmer; Routenwahl